Computed Tomographic 3-Dimensional Virtual Dissection Aiding in Diagnosis and Surgical Planning of a Rare Form of Obstructed Supracardiac Total Anomalous Pulmonary Venous Connection With an Unusual Scimitar-Like Arrangement. Issue 2 (March 2023) - Leone, David M.; Gruber, Peter J.; Pesce, Meredith; Lee, Madonna; Brown, Cary; Ghiroli, Stephen; Steele, Jeremy M.
We present a case of a newborn with a rare presentation of obstructed supracardiac total anomalous pulmonary venous connection who required emergent cannulation to extracorporeal membrane oxygenation (ECMO). Computed tomographic angiography of the heart was performed and using novel virtual dissection techniques aided in surgical planning and guidance. Computed tomographic angiography can be successfully performed in neonates with complex congenital heart disease on ECMO without adjustment of flows to aid in surgical management and novel virtual dissection techniques aid in complex anatomical delineation and spatial orientation with noncardiac structures. The preoperative imaging in this case allowed for appropriate and detailed presurgical planning and contributed to the excellent outcome of this patient.